1977
DOI: 10.1111/j.1365-2141.1977.tb00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Dysfibrinogenaemia in Acute and Chronic Liver Disease

Abstract: Plasma from patients with both acute and chronic liver disease has been examined for evidence of acquired dysfibrinogenaemia, using electrophoretic methods and coagulation tests. An examination of isolated fibrins upon SDS polyacryamide gel electrophoresis failed to demonstrate any molecular or structural defect associated with the polypeptide chains of the patients' fibrinogen or fibrinogen derivatives produced by thrombin or plasmin. However, purified fibrin monomers isolated from plasma using both Reptilase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…6 The mechanism by which abnormal fibrinogen molecules are produced is not known. Barr et al 7 postulated that dysfibrinogenemia in liver disease results from derepression of fetal gene coding of hepatocytes for fibrinogen production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The mechanism by which abnormal fibrinogen molecules are produced is not known. Barr et al 7 postulated that dysfibrinogenemia in liver disease results from derepression of fetal gene coding of hepatocytes for fibrinogen production.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of abnormal fibrinogen molecules has been reported in hepatocellular carcinoma 7 and in acute and chronic liver diseases. 6 The abnormal fibrinogen molecule is synthesized by regenerating liver cells, and it consistently interferes with fibrin monomer polymerization, resulting in prolonged PT and APTT tests. Results of plasma mixing tests, done by mixing various amounts of the patient's plasma and normal plasma pool and performing PT and APTT tests on each specimen of mixed plasmas, show that with the 50/50 mix the PT time was corrected to 14.5 sec from 25 sec and the APTT time corrected to 38 sec from 110 sec.…”
mentioning
confidence: 99%
“…Most workers agree that the defect of fi brin formation in liver disease is due to abnormal FMP [3,11]. Recent reports have suggested that the DF of liver disease is char acterised by an increase in fibrinogen-bound sialic acid content [8.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired disorders in fibrinogen (dysfibrinogenaemia) are sometimes caused by liver disease, biliary tract disease and certain malignancies, such as hepatoma and renal cell carcinoma [45,46] In addition, it has been reported that patients who underwent organ (e.g. liver) or stem cell transplantation may develop dysfibrinogenaemia [47,48].…”
Section: Acquired Disordersmentioning
confidence: 99%